The adverse effects of chronic low-dose exposure to nonylphenol on type 2 diabetes mellitus in high sucrose-high fat diet-treated rats. Issue 1 (2nd January 2018) - Yu, Jie; Yang, Jin; Luo, Ya; Mengxue, Yang; Li, Wenmei; Yang, Yu; He, Liting; Xu, Jie
ABSTRACT: Objectives : Although it has been shown that exposure to environmental endocrine disruptors (EDCs) has been implicated as a potential risk factor for metabolic disease, information on adverse effect of chronic low-dose exposure to nonylphenol (NP), on the development and progress of type 2 diabetes mellitus (T2DM) is scarce. NP, as an EDC, is a ubiquitous degradation product of nonylphenol polyethoxylate (NPE) that is primarily used in cleaning and industrial processes.Method : Eighty Sprague-Dawley rats were assigned into 8 groups (n = 10 per group): rats fed a normal-diet (ND) as the control (C-ND); rats fed a normal diet and were gavaged with NP at a dose level of 0.02 μg/kg/day (NP-L-ND), 0.2 μg/kg/day (NP-M-ND) or 2 μg/kg/day (NP-H-ND), respectively; rats fed a high-sucrose/high-fat diet (HSHFD) as the HSHFD control (C-HSHFD); rats fed a HSHFD and were gavaged with NP at a dose level of 0.02 μg/kg/day (NP-L-HSHFD), 0.2 μg/kg/day (NP-M-HSHFD) or 2 μg/kg/day (NP-H-HSHFD), respectively.Result : On day 180, the rats in the groups treated with NP-M-HSHFD and NP-H-HSHFD showed significant increases in body weight (p < 0.05) in comparison with the C-ND group. Fast blood glucose (FBG) level in the NP-M-HSHFD and NP-H-HSHFD groups was higher than that in the C-ND group (F = 96.17, p < 0.001). The fast serum insulin (FINS) level of rats was lower in both the NP-M-HSHFD and NP-H-HSHFD groups compared with the C-ND group (F = 145.56, p < 0.001). Serum leptin (LEP) level in both the NP-M-HSHFD and NP-H-HSHFD groups was lower when compared with the C-ND group (F = 34.62, p < 0.001). The effect of NP at the dose level of 0.2 μg/kg/day on FBG, serum FINS and LEP levels in rats was greatest among the treatment groups (p < 0.05). Oral glucose tolerance test showed increased area under the curve (AUC) in treatment groups at week 12 (p < 0.05). A decrease of pancreatic islet numbers and size was exhibited in the pancreatic tissue of NP-M-HSHFD and NP-H-HSHFD treated rats compared with C-ND treated rats. Co-exposure to NP and HSHFD causes inflammatory changes histologically.Conclusion : Chronic low-dose exposure to NP might induce impaired glucose tolerance, which further lead to insulin resistance, and pancreatic β cell insulin secretion deficiency, ultimately increase the risk of T2DM. Moreover, additive toxic effects of NP and HSHFD on pancreatic beta-cell function and glucose metabolism have been identified in rats as well.